Implementasi Model Kooperatif Tipe Team Games Tournament Berbasis Media Wordwall dalam Pembelajaran Menyusun Teks Deskripsi - Ntelu, Asna; Bagtayan, Zilfa Achmad; Nuramila, Nuramila (Ideas Publishing, 2025)
The background of this research is the discovery of students who find it difficult to understand and compose descriptive text due to a lack of enthusiasm in students due to inappropriate learning models. The aim of this research is to describe (1) the implementation of the Team Games Tournament type cooperative model based on Wordwall media in learning to compose descriptive texts for class VII students at SMP Negeri 3 Satap Bonepantai, (2) the ability of class VII students at SMP Negeri 3 Satap Bonepantai in compiling descriptive texts, (3) factors that influence the implementation of the Team Games Tournament type cooperative model based on Wordwall media in learning to compose descriptive text. This research uses descriptive methods. The results of the research show that (1) the implementation of the TGT type cooperative model based on Wordwall media in learning to compose descriptive text is categorized as complete, (2) The students' ability to compose descriptive text is categorized as very good, (3) Factors that influence the success of implementing the Wordwall media based TGT type cooperative model (a) ability to understand learning models and media, (b) availability of facilities and access to technology, (c) knowledge, motivation, creativity and student cooperation, (d) conducive learning atmosphere, (e) preparation of learning designs and materials appropriate (f) limitations time